66‐2: Invited Paper: QD‐Based Sensors for Infrared Imaging. Issue 1 (28th June 2021) - Malinowski, Pawel E.; Lee, Jiwon; Georgitzikis, Epimitheas; Pejovic, Vladimir; Lieberman, Itai; Ke, TungHuei; Li, Yunlong; Verschooten, Tom; Thijs, Steven; Cheyns,; David
Abstract : Quantum dots (QD) have seen a rapid uptake in display applications, especially as photoluminescent color conversion layers. In parallel, QD absorbers promise efficient photodetector components, with absorption peak tunability and monolithic integration. In this paper, we describe QD stack integration into infrared imagers, enabling accessible sensors for various display interfaces.